PENGARUH HOME VISIT METHOD DIMASA PANDEMI COVID-19 TEMA INDAHNYA KERAGAMAN NEGERIKU TERHADAP HASIL BELAJAR KELAS IV SDN BANGSALREJO KABUPATEN PATI - Anggraeni, Septiana Dinda; Saputra, Henry Januar; Reffiane, Fine (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
The Influence of Home Visit Method During Covid-19 Pandemic Theme of The beauty My Country’s Diversity on Learning Outcomes For Grade 4 SDN Bangsalrejo Pati District. the purpose of this study was to determine the influence of home visit method during covid-19 pandemic theme of the beauty my country’s diversity on learning outcomes for grade 4 SDN Bangsalrejo Pati district. This type of reserch is a quantitative pre-experimental design research with a one group pretest posttest research design. The results of data analysis after testing the phypothesis with simple linear regression analysis, it is known that the influence of variable x on variable y is seen from the coefficient of determination of 70,5%. Then the results of the calculation of the paired sample t-test the average value of the pretest learning outcomes is 58,3929 and the posttest is 74,286 with N=28, so db=28-1=27 which is obtained Tcount 9,08 with a significant level of 5% obtained Ttable 1,703. So it can be concluded that the home visit method affects the learning outcomes of grade 4 students at SDN Bangsalrejo Pati district.